AN ANALYSIS OF CLASSROOM INTERACTION PATTERNS APPLIED BY A THAI ENGLISH TEACHER IN AN ENGLISH FOR YOUNG LEARNER CLASSROOM AT SUANSANTI SCHOOL IN BANGKOK - Azizah Mutiara; Surono Surono (IKIP Siliwangi, 2024)
Classroom interactions are believed to play important role in determining the success of teaching and learning process. This study aims to find the types of classroom interaction pattern applied by a Thai English teacher in an EYL classroom, show the dominant pattern applied, and reveal the impacts of applying the classroom interaction patterns applied to the EYL teaching and learning. The descriptive qualitative method was used in this study. The data were gained through classroom observation and semi-structured interview involving a Thai English teacher and 42 students in class 5/2 elementary school at Suansanti school, Bangkok. This study used video recording, as the data collecting technique and analyzed by adapted Miles’ et al. (2014) procedures. The results indicate that there were five classroom interaction patterns applied by the Thai English teacher. Three dominant patterns applied were choral responses (36.52%), teacher talk (27.54%), and close-ended teacher questioning (26.96%). The patterns applied lead to the positive impacts including build a sense of comfort and belonging, promote students’ motivation, and enhance social development. However, the overuse of the pattern limits students’ individual expression and peer-to-peer interaction, leading to negative impact such as passive participation.